Comparative genomic analysis and optimization of astaxanthin production of Rhodotorula paludigena TL35-5 and Rhodotorula sampaioana PL61-2 - Patcharaporn Hoondee; Sukanya Phuengjayaem; Engkarat Kingkaew; Pornchai Rojsitthisak; Boonchoo Sritularak; Somphob Thompho; Natapol Pornputtapong; Worathat Thitikornpong; Somboon Tanasupawat (PLoS ONE, 2024)
Astaxanthin is a powerful antioxidant known to enhance skin, cardiovascular, eye, and brain health. In this study, the genome insights and astaxanthin production of two newly isolated astaxanthin-producing yeasts (TL35-5 and PL61-2) were evaluated and compared. Based on their phenotypic and genotypic characteristics, TL35-5 and PL61-2 were identified as basidiomycetous yeasts belonging to Rhodotorula paludigena and Rhodotorula sampaioana , respectively. To optimize astaxanthin production, the effects of cultural medium composition and cultivation conditions were examined. The optimal conditions for astaxanthin production in R . paludigena TL35-5 involved cultivation in AP medium containing 10 g/L glucose as the sole carbon source, supplemented with 1.92 g/L potassium nitrate, pH 6.5, and incubation at 20°C for 3 days with shaking at 200 rpm. For R . sampaioana PL61-2, the optimal medium composition for astaxanthin production consisted of AP medium with 40 g/L glucose, supplemented with 0.67 g/L urea, pH 7.5, and the fermentation was carried out at 20°C for 3 days with agitating at 200 rpm. Under their optimal conditions, R . paludigena TL35-5 and R . sampaioana PL61-2 gave the highest astaxanthin yields of 3.689 ± 0.031 and 4.680 ± 0.019 mg/L, respectively. The genome of TL35-5 was 20,982,417 bp in length, with a GC content of 64.20%. A total of 6,789 protein-encoding genes were predicted. Similarly, the genome of PL61-2 was 21,374,169 bp long, with a GC content of 64.88%. It contained 6,802 predicted protein-encoding genes. Furthermore, all essential genes involved in astaxanthin biosynthesis, including CrtE , CrtYB , CrtI , CrtS , and CrtR , were identified in both R . paludigena TL35-5 and R . sampaioana PL61-2, providing evidence for their ability to produce astaxanthin.
Keywords: Algal biology and biofuel production; Antioxidant Activity and Oxidative Stress; Polar Research and Ecology